Treatment of Cutaneous Wounds - Torquato Vieira, Julia; Nasr, Adonis; Tomasich, Flavio; Curtarelli, Arthur [UNESP]; Atolino, Rafael Nakamura [UNESP]; Abreu, Phillipe (Springer Nature, 2025)
Traumatic skin injuries are one of the most common medical emergencies, and it is impossible to think of a surgical emergency room without immediately associating it with an image of a traumatic injury.